Hubungan kualitas hidup dan faktor resiko pada usia lanjut di wilayah kerja puskesmas Tampaksiring I Kabupaten Gianyar Bali 2015 - Gede Wikananda (Intisari Sains Medis, 2017)
Aging is a process characterized by a wide range of changes that occur in an individual, both mentally, socially, and physically. Along with increasing age, it is associated with changes in the quality of life of the individual. Unfortunately, these changes tend to be associated to a less good. It is associated with various factors, such as changes in socio-economic environment in the sense to stop working due to retirement, the inability to take part in society, loss of family and friends, the dependence of physical needs, a decrease in physical conditions, and lack of attention from people around, especially families in meeting the needs of physically and mentally the elderly. This condition can cause severe morbidity for the elderly if not handled properly, causing a bad impact on quality of life for the elderly which leads to increased morbidity and mortality. Based on these problems, the authors conducted a study to determine the level of quality of life for the elderly associated with various risk factors in the elderly in Puskesmas Tampaksiring I as a step advocacy in improving the programs of promotion and prevention in dealing with problems of the elderly in Puskesmas Tampaksiring I.                This study is a cross - sectional descriptive study . Samples are elderly aged 60 years and older with a sample size of 90 people selected randomly in Tampaksiring Village and Village Sanding District Tampaksiring Gianyar regency using multistage random sampling technique. Data were obtained through interviews with respondents using a structured questionnaire.                The results showed that the lack or poor quality of life associated with the age group > 70 years, male gender, low education levels, status is not married or a widow / widower, did not work, the level of monthly income is low, and the presence of > 2 chronic disease.